Deception and self-deception - Peter Schwardmann; Joël J. van der Weele (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2017)
Why are people so often overconfident? We conduct an experiment to test the hypothesis that people become overconfident to more effectively persuade or deceive others. After performing a cognitively challenging task, half of our subjects are informed that they can earn money by convincing others of their superior performance. The privately elicited beliefs of informed subjects are significantly more confident than the beliefs of subjects in the control condition. By generating exogenous variation in confidence with a noisy performance signal, we are also able to show that higher confidence indeed makes subjects more persuasive in the subsequent face-to-face interactions.
Keywords: C91; D03; D83; 330; overconfidence; self-deception; motivated cognition; persuasion; deception